08.51: An experimental study of composite beam‐column joints subject to impact loads. (13th September 2017) - Chen, Kang; Tan, Kang Hai; Yang, Bo
ABSTRACT: Beam‐column joints are one of the key elements in steel and composite frames. Till now, many research studies have focused on the behaviour of bare steel beam‐column joints and the influence of composite slabs subjected to quasi‐static loads. In this study, the research was extended to dynamic loading condition. Two beam‐column joint specimens with composite slabs, which were designed based on Eurocode 4, were tested using an MTS drop‐weight machine. This loading condition is probably more realistic for joints under progressive collapse scenario, which is a dynamic process. One of the specimens was a middle joint subject to sagging moment. The other specimen was a side joint subject to hogging moment. Behaviour of both joint specimens, including impact force, displacement of the middle column, strain and failure mode, was presented. Differences in the behaviour of the two joint specimens were observed and explained.